A Genre Analysis Of Undergraduate Students’ Dissertation Acknowledgements In A Ghanaian University - Bikpiebyel Chelnye Ambrose (University of Cape Coast, 2024)
In recent times, researchers have focused attention on dissertation acknowledgement. Despite the scholarly attention on this sub-genre, it remains under-studied. The present study analysed the generic structure of undergraduate dissertation acknowledgements (DAs) of a Ghanaian university: S D Dombo University of Business and Integrated Development Studies. Hyland’s (2004) three-tier move structure was used in analysing the generic structure of the DAs. The study then explored the use of modal verbs in the DAs using Biber et al (1999) and Halliday’s (1994) frameworks on modality and further analysed other lexico-grammatical features based on their frequency of occurrence in the DAs using Hyland and Tse (2004) framework on lexico-grammatical patterns. The modal verbs were further analysed based on their functions in the DAs. A qualitative approach was used together with some descriptive statistics to analyse a data of 80 DAs drawn from two departments: African and General Studies (AGS) and Community Development (CD). The 80 DAs comprised 40 from each of the two departments. Three key findings were made: the DAs displayed two different move structures- a three- tier move structure and a two-move structure. Six of the central modal verbs as classified by Biber et al. (1999) featured frequently in the data and expressed multiple functions. Also, the DAs deployed various forms of lexico-grammatical features. The study has implications for research, theory and pedagogy.
xiii,151p:,ill
Keywords: Academic writing Acknowledgements Discourse community Modal verbs Modality Lexico-grammatical Features